SEARCH PRODUCTS APPLICATIONS IN METRO PACIFIC PLACE USING MACROMEDIA DREAMWEAVER 8 - Adi Kristianto; Syahril, SKom Syahril, SKom (Jurnal Sistem Informasi, 2010)
Along with the development of the age and the rapid technological and sophisticated,almost all layers of society in the world using a computer in various fields of work.One of the search process the goods in a department. Store.Goods Search application was used to facilitate the search easier time in the goodsdesired by the customer in the warehouse, which is conducted computerized.Making Application Search Products at Pacific Place Metro is using MacromediaDreamweaver 8 application program and to connect it using the PHP program.